Perkembangan E-Learning dalam Pembelajaran di Dunia - Juriana, Juriana (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2019)
E-learning is a learning that done using sophisticated electronic technology media whose learning is designed by facilitators such as teachers or lecturers without knowing distance and time which is often known as online learning. The development of e-learning started in the 1970s where learning was done remotely and assignments were coordinated and given via email. The Open University in the UK was the first college to implement distance learning due to geographical conditions and student time constraints. In Afrika, the development of e-learning began in 1886, when the electronic telecommunication cable connection was installed by the colonial authorities between Lagos and the colonial office in London to send and receive information. This case is purposed to know about how the development of e-learning in the world.